(untitled) (INNOVATIVE ECONOMY, 2020)
Ivanyshyn V.V., Voloshchuk Yu.O. LEASING AS A MECHANISM FOR UPDATING THE MATERIAL AND TECHNICAL BASE OF THE AGRO-INDUSTRIAL COMPLEX Purpose. The aim of the article is to study the essence, features, taking into account the current trends and opportunities of applied leasing as a mechanism for the formation and updating of the material and technical base and the provision of cash resources for the innovative development of the agro-industrial complex. Methodology of research. General scientific and special methods are used in the process of research, in particular: dialectic, monographic and system analysis – to substantiate the essence, generalization of the trend of leasing activity in Ukraine; economic and statistical method – to determine the level of leasing efficiency in the agro-industrial sector; abstract and logical – with the improvement of the directions and mechanisms of leasing activity in the agro-industrial complex. Findings. It is revealed that 183 legal entities – lessors, 280 financial companies with active licenses and financial leasing services and 88 banks – are included in the List of legal entities that have the right to provide financial services and are registered with the National Financial Services Commission. The vast majority of lessees are legal entities (90%), and only 10% are natural persons. Approximately 70% of active leasing clients are SMEs. It is revealed that in 2017 the machinery, machines and equipment for agriculture are provided for lease in the amount of UAH 4398.2 million (19.3% of the total value of financial leasing contracts). The value of contracts decreased by 9.2% (UAH 447.0 million) compared to the respective period of 2016. During this time, agricultural leasing was transferred to: tractors (50%); combine harvesters (25%); processing machinery (25%). It is established that the main constraining factors of the development of the leasing industry in Ukraine are: lack of awareness of the advantages of leasing to finance business expansion; absence of favorable legal and tax base; lack of domestic and foreign capital for leasing companies and lack of programs aimed at leasing for SMEs; the separation of the leasing industry from international trends and developments. It has been determined that leasing is one of the mechanisms for introducing innovations into agriculture, which helps to quickly solve the problem of modernization, improvement of the material and technical base, facilitate the development of production and sales processes, and, accordingly, increase the number of jobs. It is a financial instrument that will help to renovate outdated production facilities and update infrastructure in the context of economic development and Ukraine’s entry into the structure of the world market. Originality. Further development of the trend of using leasing as a mechanism for updating the material and technical base of agriculture and the ability of the system with the help of leasing to provide financial resources for innovative development, as well as systematization of the legislative framework in the field of leasing; definition of directions of activation of leasing activity in Ukraine. Practical value. The obtained results of the research can be used to increase the use of leasing in solving the problem of improving the structure of the material and technical base of agricultural enterprises. Key words: leasing; financing; material and technical base; innovations; agriculture; capital.